Transcriptomic analysis reveals mechanisms for the different drought tolerance of sweet potatoes - Liu, Enliang; Xu, Linli; Luo, Zhengqian; Li, Zhiqiang; Zhou, Guohui; Gao, Haifeng; Fang, Furong; Tang, Jun; Zhao, Yue; Zhou, Zhilin; Jin, Ping (Frontiers in Plant Science, 2023)
Drought is a common environmental stress with great negative impacts on plant growth, development and geographical distribution as well as agriculture and food production. Sweet potato is characterized by starchy, fresh and pigmented tuber, and is regarded as the seventh most important food crop. However, there has been no comprehensive study of the drought tolerance mechanism of different sweet potato cultivars to date. Here, we studied the mechanism for drought response of seven sweet potato drought-tolerant cultivars, which were classified into four groups of drought tolerance performance based on the drought coefficients and physiological indicators. A large number of new genes and transcripts were identified by transcriptome sequencing, with an average of about 8000 new genes per sample. Alternative splicing events in sweet potato, which were dominated by first exon and last exon alternative splicing, were not conserved among different cultivars and not significantly affected by drought stress. Furthermore, different drought-tolerance mechanisms were revealed through differentially expressed gene analysis and functional annotation. Two drought-sensitive cultivars, Shangshu-9 and Xushu-22, mainly resisted drought stress by up-regulating plant signal transduction. The other drought-sensitive cultivar Jishu-26 responded to drought stress by down-regulating isoquinoline alkaloid biosynthesis and nitrogen/carbohydrate metabolism. In addition, the drought-tolerant cultivar Chaoshu-1 and drought-preferred cultivar Z15-1 only shared 9% of differentially expressed genes, as well as many opposite metabolic pathways in response to drought. They mainly regulated flavonoid and carbohydrate biosynthesis/metabolism in response to drought, while Z15-1 increased photosynthesis and carbon fixation capacity. The other drought-tolerant cultivar Xushu-18 responded to drought stress by regulating the isoquinoline alkaloid biosynthesis and nitrogen/carbohydrate metabolism. The extremely drought-tolerant cultivar Xuzi-8 was almost unaffected by drought stress and responded to drought environment only by regulating the cell wall. These findings provide important information for the selection of sweet potatoes for specific purposes.